(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
There are some reasons for the development of cross bite: inflammation and the resulting violation of jaw growth, reduction of chewing function or chewing on one side, violation of the timing and sequence of teething, non-wrinkled tubercles of milk teeth and uneven contact of dental lines, violation of nasal breathing, improper swallowing; common diseases associated with impaired calcium metabolism; congenital clefts of the sky, impaired miodynamic balance, consequences of injuries. Common causes of cross-bite are disorders in the musculoskeletal system, dysplastic diseases, systemic damage to the entire skeleton, including the dental apparatus. Delayed diagnosis cross-bite increases the terms of treatment and social adaptation of the child.